1981
DOI: 10.2307/2232499
|View full text |Cite
|
Sign up to set email alerts
|

Imitation Costs and Patents: An Empirical Study

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
422
0
16

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 979 publications
(452 citation statements)
references
References 13 publications
14
422
0
16
Order By: Relevance
“…Microeconomic empirical studies of patenting in the US by Scherer et al 1959, (Patents and the Corporation, Boston, privately published) and (Mansfield E. et al, 1981), (Mansfield Edwin, 1985a) and Mansfield (1986) and in the UK Taylor and Silberston,1973) called in doubt the hypothesis that patents protect effectively innovations from innovation. The studies also showed that patent protection is important only in a few industries, most notably in pharmaceuticals.…”
Section: The Use Of Ip Rights In the Usmentioning
confidence: 99%
“…Microeconomic empirical studies of patenting in the US by Scherer et al 1959, (Patents and the Corporation, Boston, privately published) and (Mansfield E. et al, 1981), (Mansfield Edwin, 1985a) and Mansfield (1986) and in the UK Taylor and Silberston,1973) called in doubt the hypothesis that patents protect effectively innovations from innovation. The studies also showed that patent protection is important only in a few industries, most notably in pharmaceuticals.…”
Section: The Use Of Ip Rights In the Usmentioning
confidence: 99%
“…The risk to having competitors "inventing around" and the disclosure of critical information are the most important reasons patents are not always considered as an efficient protection mechanism of innovation rents (Levin et al 1987;Scotchmer and Green 1990;Cohen et al 2000). This is illustrated by Mansfield et al (1981), who find that patent protection does not increase imitation time and costs dramatically. Firms that perceive a higher "ineffectiveness" of the patent system and a higher cost of patenting are therefore likely to patent less than other firms.…”
Section: Hypothesis 1amentioning
confidence: 99%
“…However, the value of a patent will depend on the type of technology it protects and the existing capacity that the organization has for defending the patent in question (Mansfield, 1981). More important than patenting per se, is the ability of the university to actively search among its research activities for developments with the potentia l for commercialization, and to provide researchers with the resources necessary to accomplish them.…”
Section: Designing and Fitting Odus Within The University Structurementioning
confidence: 99%